Role of the ectoparasitoid, Choetospila elegans Westwood (Hymenoptera: Pteromalidae) in suppression of Sitophilus oryzae (L.) (The Journal of Plant Protection Sciences, 2022)
Biocontrol agents like beneficial insects, para sitoids, predators, pathogens etc. are essential  elements of biological control of insect pests  (6). Success of using this parasitoid in biocon trol programme usually depends not only on  the availability of their insect hosts but some times on a complex system of other factors  such as additional food sources, alternate  hosts and shelter (5,6). Earlier research work ers (3,1,2) indicated that the most favourable  combinations of natural enemies would be  those that tend to parasitize or prey on differ ent optimum/suitable stages of the host.
Keywords: parasitoids; Choetospila elegans